2011
DOI: 10.1007/s00705-010-0905-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of a human rabies virus from Sri Lanka

Abstract: The complete genome sequence of a human rabies virus, strain H-08-1320, from Sri Lanka was determined and compared with other rabies viruses. The size of the genome was 11,926 nt, and it was composed of a 58-nucleotide 3' leader, five protein genes--N (1353 nt), P (894 nt), M (609 nt), G (1575 nt), and L (6387 nt)--and a 70-nt 5' trailer. The intergenic region G-L contained 515 nt. The sizes of the nucleoprotein, phosphoprotein, matrix-protein, glycoprotein and large-protein was 450, 296, 202, 524 and 2,128 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…To date, several methods, such as rapid amplification of cDNA (RACE) [22-24] and gene-walking approach have been employed to obtain the whole genome sequence, including the 5' and 3' untranslated regions (UTR). In the present study, a simple method of amplification and sequencing of full length of rabies virus genome was performed, according to reference 7.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several methods, such as rapid amplification of cDNA (RACE) [22-24] and gene-walking approach have been employed to obtain the whole genome sequence, including the 5' and 3' untranslated regions (UTR). In the present study, a simple method of amplification and sequencing of full length of rabies virus genome was performed, according to reference 7.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used for complete genome sequencing of MLB2 were designed using reported sequences (9, 10). The terminal parts were amplified using a rapid amplification of cDNA ends kit, and the PCR products were purified and sequenced (13). …”
Section: Genome Announcementmentioning
confidence: 99%
“…Further, phylogeny using the partial nucleoprotein sequences must be used with caution as they are less reliable than using the complete nucleoprotein coding region [5]. Recently, Matsumoto et al [7] reported that the Sri Lankan isolates formed an independent lineage and did not cluster with Indian viruses while using full genome sequences for phylogeny. However the authors themselves suggested that the limited number of Indian viruses used in their study may not be from the southern part of India.…”
mentioning
confidence: 99%